Pubic spread development and first egg lay in Japanese quail - Satterlee, Daniel G. (2004)
Measurement of the space between the pelvic ("pin") bones, also known as pubic spread (PS), is used to determine the state of sexual development of female broiler breeders. Herein, we examined PS at selected intervals before, during, and after puberty in Coturnix, an avian species often used for extrapolation of data to more valuable poultry stocks. The PS was determined using different sets of wooden applicator sticks joined together to represent fixed gauges of increasing widths. These gauges were placed between the pelvic pin bones of individual quail until the best fit was detected. Within a bird (n = 80), PS measurements were made at 15 different ages (beginning at 21 and ending at 84 d of age). A cubic relationship was found to exist between age and PS. The best-fit curve of this relationship showed that little development in PS was evident between 21 to 38 d (prepubescence), rapid and increasing development occurred between 38 to 59 d, and no further development occurred from 59 to 84 d of age (postpubescence). Regressions of PS with age at first egg showed that the optimum age range to make a PS measurement to predict the onset of egg lay was sometime during 49 to 52 d of age. The data demonstrate the usefulness of making pubic measurements in Japanese quail to evaluate sexual development and to predict the initiation of egg lay.